(untitled) (REVISTA DE AGRICULTURA NEOTROPICAL, 2023)
Knowledge of soil attributes is a basic premise when defining land use systems, as well as in the monitoring of the properties and/or quality indicators of the cropping systems implemented. The objective of this study was to characterize the physical and chemical attributes of Argissolo and Gleissolo in areas under different uses and landforms in the municipality of Areia, PB, Brazil. Areas with different uses were selected, such as banana (Musa parasidiaca), pasture (Brachiaria brizantha), reforestation with ‘sabiá’ (Mimosa caesalpiniaefolia), and open tropical forest, as well as two relief positions (foothill and mid-slope). Samples were taken from the 0.00-0.20 and 0.20-0.40 m layers. The samples were then air-dried, crumbled, and passed through a sieve with a 2 mm mesh to obtain fine air-dried soil. Physical, chemical, and fertility analyses were carried out and cation exchange capacity, sum of bases, and base saturation were calculated. According to the results, in general, the soil physical and chemical attributes were altered by land use and landforms. Soil organic matter levels in the surface layer were higher in the deposition foothills, while in the mid-slope the forest environments (natural or forested) showed higher levels of organic matter.